Governance, Regulation, and Green Banking Disclosure: An Empirical Study of Indonesian Banks - Silalahi, Dumariani; Silalahi, Harlen; Barus, Berlin; Sitompul, Ganda Tua; Sinulingga, May Happy Stephany Br (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to analyze the influence of corporate governance on green banking disclosure in the Indonesian banking sector, focusing on three key variables: board size, the proportion of independent commissioners, and the presence of female directors. It also examines the moderating role of green banking regulation, particularly following the issuance of Financial Services Authority Regulation No. 51/POJK.03/2017 on Sustainable Finance. The analysis is based on secondary data from 237 bank-year observations of publicly listed banks on the Indonesia Stock Exchange during the period 2007–2021, using the Ordinary Least Squares (OLS) method. The results show that board size, the proportion of independent commissioners, and the presence of female directors each have a significant negative effect on green banking disclosure. However, the implementation of green banking regulation is found to mitigate the negative effect of board size, indicating that regulatory frameworks can enhance the effectiveness of governance in promoting environmental transparency. In contrast, the regulation does not significantly moderate the effects of independent commissioners or female directors. These findings offer empirical evidence on the interaction between corporate governance and environmental regulation, and highlight the strategic role of regulatory intervention in supporting transparency and green initiatives within the banking industry. Keywords: corporate governance, green banking disclosure, green banking regulation